Searching for Dasein: Positive Science’s Failure to Become the Philosophical Locus of Natural Knowledge Universality - VOLLET, Lucas Ribeiro (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
I will argue in this article, using mainly Heideggerian conceptual apparatus that positive science has failed to represent the philosophical locus to ground the phenomenological-essential structure of the universality of human knowledge of the natural world. To show the phenomenological structure of the synthetic a priori judgments of natural science, Kant tried to substitute metaphysics through transcendental philosophy, but he only managed to develop the programmatic form of philosophical questioning. That programmatic account has not yet formed the objective historical consciousness of the universality of natural science. It is the mere “possible experience” of a subject. I will argue that subjective possible experience cannot give a historical perspective on the universality of scientific possibilities. It is, therefore, an incomplete property for the phenomenological codification of the intentional unity of meaning of the natural science content. The result is a void of ontological parameters for judging natural science’s role in our culture as the highest instance of universal knowledge.